Remedy for Radiation Fear - Discard the Politicized Science - Jerry M. Cuttler (SAGE Publishing, 2014)
The great tragedy of science-the slaying of a beautiful hypothesis by an ugly fact. -Huxley TH. English biologist (1825-1895) Seeking a remedy for the radiation fear in Japan, the author re-examined an article on radiation hormesis. It describes the background for this fear and evidence in the first UNSCEAR report of a reduction in leukemia of the Hiroshima survivors in the low dose zone. The data are plotted and dose-response models are drawn. While UNSCEAR suggested the extra leukemia incidence is proportional to radiation dose, the data are consistent with a hormetic J -shape and a threshold at about 100 rem (1 Sv). UNSCEAR data on lifespan reduction of mammals exposed continuously to gamma rays indicate a 2 gray/year threshold. This contradicts the conceptual basis for radiation protection and risk determination established in 1956-58. In this paper, beneficial effects and thresholds for harmful effects are discussed, and the biological mechanism is explained. The key point: the rate of DNA damage (double-strand breaks) caused by background radiation is 1000 times less than the endogenous (spontaneous) rate. It is the effect of radiation on an organism's very powerful adaptive protection systems that determines the dose-response characteristic. Low radiation up-regulates the protection systems, while high radiation impairs these systems. The remedy for radiation fear is to expose and discard the politicized science.